Bez znieczulenia Without anesthesia - Wajda, Andrzej, 1926-; Holland, Agnieszka, 1948-; Film Polski; New Yorker Video (Firm) (New York, NY : New Yorker Video, 1995)
Tells the story of Jerzy, a famous journalist just returned from as assignment abroad. Despite his success, his wife leaves him for an obnoxious young writer and refuses to explain why. Against everyone's advice, Jerzy fights the divorce and searches in vain for an explanation for why she left. At the same time, Jerzy finds that he has fallen out of official favor, for reasons no less mysterious.
In Polish with English subtitles.
Released in 1981 as a motion picture.
"NYV 32295"--Cassette label and container.
Cinematography, Edward Klosinski ; editor, Halina Prugar ; music, Jerzy Derfel, Wojciech Mynarski ; production manager, Barbara Pec-Slesicka.
Zbigniew Zapasiewicz, Ewa Dalkowska, Andrzej Seweryn, Krystyna Janda.
VHS.
Keywords: Feature films